2019
DOI: 10.1016/j.nut.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Sweet taste perception is greater in non-Hispanic black than in non-Hispanic white adults

Abstract: Objective: Research suggests a difference in sweet taste perception between non-Hispanic Black (NHB) and non-Hispanic White (NHW) adults, but limited research has examined sweet taste perception in relation to dietary intake of sweet products. Research Methods and Procedures: This cross-sectional study examined the association between race, sweet taste perception and sweet food, beverage, and sugar consumption in healthy, NHB and NHW adults. Seven-day food records were analyzed in Nutrition Data System for Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Perceived intensity of taste and other oral sensations has been shown to vary greatly among individuals and may be one of the most important determinants of food preference and consumption affecting nutritional and health status (Stewart et al, 2010, Ullrich et al, 2004. Many factors have been shown to affect perceived taste intensity perception such as health status (Overberg et al, 2012, Berteretche et al, 2004, age (Bilash et al, 1959, Mojet et al, 2001, Monteleone et al, 2017, Vignini et al, 2019, gender (Hirokawa et al, 2006, Michon et al, 2009, Bartoshuk et al, 1994, Monteleone et al, 2017, Vignini et al, 2019, ethnicity (Williams et al, 2016, Bowser et al, 2019, genetics (Kim et al, 2003b, Chen et al, 2009 and taste phenotypes (Yang et al, 2014, Bajec and Pickering, 2008, Dinnella et al, 2018, Yang et al, 2019. Findings, however, are often conflicting across different studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived intensity of taste and other oral sensations has been shown to vary greatly among individuals and may be one of the most important determinants of food preference and consumption affecting nutritional and health status (Stewart et al, 2010, Ullrich et al, 2004. Many factors have been shown to affect perceived taste intensity perception such as health status (Overberg et al, 2012, Berteretche et al, 2004, age (Bilash et al, 1959, Mojet et al, 2001, Monteleone et al, 2017, Vignini et al, 2019, gender (Hirokawa et al, 2006, Michon et al, 2009, Bartoshuk et al, 1994, Monteleone et al, 2017, Vignini et al, 2019, ethnicity (Williams et al, 2016, Bowser et al, 2019, genetics (Kim et al, 2003b, Chen et al, 2009 and taste phenotypes (Yang et al, 2014, Bajec and Pickering, 2008, Dinnella et al, 2018, Yang et al, 2019. Findings, however, are often conflicting across different studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have found that women tend to be more sensitive to taste compared to men (Hirokawa et al, 2006), whilst other studies failed to reveal a significant effect (Chang et al, 2006, Melis et al, 2013. In general, some significant effects of ethnicity on perceived taste intensity have been observed (Williams et al, 2016, Bowser et al, 2019, but there is a lack of research comparing Asian and Caucasian populations. It is worth noting that some of the earlier studies used a relatively small sample size, which could contribute to conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…Further, we cannot rule out that different gLMS ratings and chemesthetic sensations for ibuprofen between individuals of African and European genetic ancestry may be due to nongenetic factors, as self-identified race/ethnicity is highly correlated with genetic ancestry. Research has shown that Americans who self-reported as Black most preferred significantly higher levels of sweetness [35] and had higher daily intakes of added sugar [36] than those who self-reported as White. While our evidence suggests that adults with African genetic ancestry perceived the pediatric formulation of ibuprofen differently than did those of European genetic ancestry, future association studies on taste and palatability need to include children and other age groups to determine the relative contributions of cultural-dietary, developmental, genetic, and epigenetic pathways [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Further on, it was shown that another factor can influence the intensity of perception of the sweet taste, which is ethnicity. In fact, the study by Bowser et al (2019) revealed that the black participants have a greater intensity of sweet taste perception than whites:…”
Section: Introductionmentioning
confidence: 99%